2022
DOI: 10.1155/2022/4046966
|View full text |Cite|
|
Sign up to set email alerts
|

Study on Fault Diagnosis Method and Application of Automobile Power Supply Based on Fault Tree-Bayesian Network

Abstract: Among various fault types of automotive power faults, power supply UB + faults have the most complex relationship between fault signs and fault points and are difficult to diagnose. So this paper proposes a Bayesian network fault diagnosis model of automobile power supply based on fault tree. Firstly, based on the in-depth analysis of the principle of automobile power supply fault, the UB + fault tree model is constructed. The fuzzy Bayesian network model of UB + fault is constructed through the mapping relati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…The Bayesian network can be used to perform probabilistic inference and is constructed by domain experts. There is a correspondence between the Bayesian network and the fault tree [34]. The transformation relationship between the fault tree and the Bayesian network is as follows: (1) The bottom event in the fault tree corresponds to the parent node in the Bayesian network; (2) The top event in the fault tree corresponds to the child nodes in the Bayesian network; (3) Logical gates in the fault tree correspond to conditional probability tables of nodes in Bayesian networks.…”
Section: ➢ Correspondence Between Fta and Bayesian Networkmentioning
confidence: 99%
“…The Bayesian network can be used to perform probabilistic inference and is constructed by domain experts. There is a correspondence between the Bayesian network and the fault tree [34]. The transformation relationship between the fault tree and the Bayesian network is as follows: (1) The bottom event in the fault tree corresponds to the parent node in the Bayesian network; (2) The top event in the fault tree corresponds to the child nodes in the Bayesian network; (3) Logical gates in the fault tree correspond to conditional probability tables of nodes in Bayesian networks.…”
Section: ➢ Correspondence Between Fta and Bayesian Networkmentioning
confidence: 99%
“…Security and Communication Networks has retracted the article titled "Study on Fault Diagnosis Method and Application of Automobile Power Supply Based on Fault Tree-Bayesian Network" [1] due to concerns that the peer review process has been compromised. Following an investigation conducted by the Hindawi Research Integrity team [2], signifcant concerns were identifed with the peer reviewers assigned to this article; the investigation has concluded that the peer review process was compromised.…”
mentioning
confidence: 99%